Implementasi Pendekatan Kontekstual pada Pembelajaran Bahasa Indonesia di Kelas IIB MIS Mutiara Aulia - Lubis, Nailah Rizkiyah; Wandini, Rora Rizki; Nst, Mona Hijriah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to find out how teachers implement contextual approaches in the classroom. The research method used is field qualitative. By using this method, researchers obtain data through interviews, observations, and direct documentation in the field. The results of the study show that the Contextual Teaching and Learning (CTL) approach is very effective and efficient in the learning process. Students find it easier to understand the learning material because it is related to their daily lives. This learning approach is expected to encourage students to create and learn knowledge independently, as well as educate and motivate them to apply that knowledge in real life.